2020
DOI: 10.1186/s13071-020-04248-2
|View full text |Cite|
|
Sign up to set email alerts
|

First multilocus sequence typing (MLST) of Giardia duodenalis isolates from humans in Romania

Abstract: Background: Giardia duodenalis is one of the most prevalent and highly diverse human parasites, encompassing a complex of eight genetically distinct assemblages, each further divided into sub-assemblages. While in recent years, G. duodenalis genotype distribution patterns in humans have been intensely studied, there is still very little information available on the diversity of Giardia genotypes and sub-assemblages infecting people in Romania. In the present study, we investigated the genetic diversity of Giar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 44 publications
2
20
0
1
Order By: Relevance
“…Assemblage B infections have a higher parasitic load and increased rate of cyst shedding which would explain the higher detection rates in comparison to assemblage A infections ( Kohli et al, 2008 ). Yet higher rates of assemblage A infections have been observed in countries such as Brazil ( Souza et al, 2007 ), Ethiopia ( Damitie et al, 2018 ), Iran ( Kasaei et al., 2018 ; Mahmoudi et al, 2020 ), New Zealand ( Winkworth et al., 2008 ), Syria ( Skhal et al., 2017 ) and Romania ( Costache et al., 2020 ). Due to limited molecular epidemiological studies of giardiasis in humans, an accurate geographical pattern for individual G. intestinalis assemblages cannot be concluded.…”
Section: International Prevalence Of Giardia Assem...mentioning
confidence: 99%
See 2 more Smart Citations
“…Assemblage B infections have a higher parasitic load and increased rate of cyst shedding which would explain the higher detection rates in comparison to assemblage A infections ( Kohli et al, 2008 ). Yet higher rates of assemblage A infections have been observed in countries such as Brazil ( Souza et al, 2007 ), Ethiopia ( Damitie et al, 2018 ), Iran ( Kasaei et al., 2018 ; Mahmoudi et al, 2020 ), New Zealand ( Winkworth et al., 2008 ), Syria ( Skhal et al., 2017 ) and Romania ( Costache et al., 2020 ). Due to limited molecular epidemiological studies of giardiasis in humans, an accurate geographical pattern for individual G. intestinalis assemblages cannot be concluded.…”
Section: International Prevalence Of Giardia Assem...mentioning
confidence: 99%
“…There is speculation that mixed assemblage infections are being underreported due to the preferential amplification of one assemblage over the other depending on the primer set being used ( Wielinga & Thompson, 2007 ). Moreover, primers used for typing G. intestinalis not only differ in their specificities (see Table 1 ) but have been reported to have variable amplification success rates ( Costache et al., 2020 ; Chourabi et al., 2021 ; Iwashita et al, 2021 ).…”
Section: Molecular Tools For Genetic Characterisation Of G ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The increased percentage of assemblage B over A is in line with the reports from previous studies ( van der Giessen et al., 2006 ; Hijjawi et al., 2016 ; Nunes et al., 2018 ). Although most studies have reported assemblage B to be more prevalent in both developed and developing countries ( Costache et al., 2020 ; Messa et al., 2021 ), other studies have found a predominance of assemblage A ( Thompson, 2000 ; Asher et al., 2016 ). It was suggested that the relatively high percentage of assemblage B may be attributable to the technical tools used to detect G. duodenalis.…”
Section: Discussionmentioning
confidence: 92%
“…Following publication of the original article [ 1 ], it was brought to our attention that incorrect primers information had been provided in Table 1 .…”
Section: Correction To: Parasites Vectors 13 387 (2020) Https://doiorg/101186/s13071-020-04248-2mentioning
confidence: 99%